Effects of resting heart rate on blood pressure and hypertension in Chinese children: findings from blood pressure surveillance program. (17th February 2019) - Hu, Jia; Teng, Chen-gang; Chu, Guang-ping; Han, Di; Fu, Han; Zhou, Yi-kai; Wang, Qi; Wang, Bo; Shen, Hui; Liu, Fang; Yang, Hai-bing
ABSTRACT: The purpose of this study was to analyze the association between resting heart rate (RHR) and prevalence of hypertension in Chinese children and to identify if this association was mediated by body mass index (BMI). The data of 5445 children who participated in the Blood Pressure Surveillance Program (2011–2017) were analyzed in this study. Children were divided into four groups according to quartiles of RHR in boys and girls, respectively. Compared to those in the first quartile, boys and girls in the fourth quartile were 3.06 (95% CI 2.12, 4.41) and 4.94 (95% CI 3.21, 7.61) times more likely to have hypertension, respectively. Meanwhile, every 10 beats per minute (bpm) increase in RHR was associated with a 41% (95% CI 1.27, 1.56) and 66% (95% CI 1.49, 1.85) greater risk of hypertension in boys and girls, respectively. There were no significant interactions between RHR and BMI on the prevalence of hypertension. This study confirms the existence of a relationship between elevated RHR and increased risk of hypertension in children, independent of BMI. An elevated RHR could be considered as a risk factor for the risk assessment of hypertension, no matter from a clinical setting or a public health perspective.